A mechanosensitive Ca2+ channel activity is dependent on the developmental regulator DEK1. Issue 1 (December 2017) - Tran, Daniel; Galletti, Roberta; Neumann, Enrique; Dubois, Annick; Sharif-Naeini, Reza; Geitmann, Anja; Frachisse, Jean-Marie; Hamant, Olivier; Ingram, Gwyneth
Abstract Responses of cells to mechanical stress are thought to be critical in coordinating growth and development. Consistent with this idea, mechanically activated channels play important roles in animal development. For example, the PIEZO1 channel controls cell division and epithelial-layer integrity and is necessary for vascular development in mammals. In plants, the actual contribution of mechanoperception to development remains questionable because very few putative mechanosensors have been identified and the phenotypes of the corresponding mutants are rather mild. Here, we show that theArabidopsis Defective Kernel 1 (DEK1) protein, which is essential for development beyond early embryogenesis, is associated with a mechanically activated Ca2+ currentin planta, suggesting that perception of mechanical stress plays a critical role in plant development. A rise in cytoplasmic Ca2+ concentration is a well-described response of plant cells to mechanical stimulation. Here the authors show that the DEK1 protein, which is essential for epidermis specification and development in plants, is required for triggering a mechanically-activated Ca2+ channel.